Pameran maya: blockchain technology / Perpustakaan Tengku Anis - UiTM Kelantan, Perpustakaan Tengku Anis (Perpustakaan Tengku Anis (PTA), 2022)
Blockchain is a shared, immutable ledger that aids the process of recording transactions and tracking assets in a business network. An asset might be material (a house, car, cash, land) or intangible (intellectual property, patents, copyrights, branding). Virtually anything of value can be tracked and traded on a blockchain network, reducing risk and cutting costs for all involved. The importance of blockchain: information is the lifeblood of business. The faster and more accurate it is received, the better. Because it delivers immediate, shareable, and entirely transparent information kept on an immutable ledger that can only be viewed by permissioned network users, blockchain is excellent for delivering that information. A blockchain network can track orders, payments, accounts, production and much more. You can see all details of a transaction end to end because members share a single view of the truth, giving you greater confidence as well as new efficiencies and opportunities.